NEW SAMPLE PREPARATION LINE FOR RADIOCARBON MEASUREMENTS AT THE GXNU LABORATORY. Issue 6 (30th May 2022) - Shen, Hongtao; Tang, Junsen; Wang, Li; Qi, Mingli; Li, Zhaomei; Wei, Siyu; Sasa, Kimikazu; Shi, Shulin; Zhang, Guofeng; Chen, Dingxiong; Qi, Linjie; Wang, Ning; et al.
ABSTRACT: A new system for preparing 14 C samples was established for a compact accelerator mass spectrometer (GXNU-AMS) at Guangxi Normal University. This sample preparation system consists of three units: a vacuum maintenance unit, a CO2 purification unit, and a CO2 reduction unit, all of which were made of quartz glass. A series of radiocarbon ( 14 C) preparation experiments were conducted to verify the reliability of the system. The recovery rate of graphite obtained was more than 80%. The carbon content in the commercial toner and wood sample was linearly fitted to the CO2 pressure in the measurement unit of the system. The results showed a good linear relationship, indicating that the reliability of the sample preparation system. AMS measurements were conducted on a batch of standard, wood, and dead graphite samples prepared using this system. The results showed that the beam current of 12 C- for each sample was more than 40 μA, the carbon contamination introduced during the sample preparation process was ∼ 2 × 10 –15, and that the new sample preparation system is compact, low-contamination, and efficient and meets the GXNU-AMS requirements for 14 C samples.